Sagot :
Answer:
1. (a+8)(a-5)
FOIL METHOD:
(a)(a) = a²
(a)(-5) = -5a
(8)(a) = 8a
(8)(-5) = -40
Solve like terms,
-5a + 8a = 3a
FINAL ANSWER = a² + 3a - 40
2. (x-4)(x-8)
FOIL METHOD
(x)(x) = x²
(x)(-8) = -8x
(-4)(x) = -4x
(-4)(-8) = 32
Solve like terms,
-8x - 4x = -12x
FINAL ANSWER: x² - 12x + 32
Answer:
[tex]1. (a + 8)(a - 5)[/tex]
[tex](a + 8) \times (a - 5)[/tex]
Multiply each term in the first parenthesis by each term in the second parenthesis (FOIL).
[tex]a \times a - 5a + 8a - 8 \times 5[/tex]
Calculate the product
[tex]a {}^{2} - 5a + 8a - 8 \times 5[/tex]
[tex]a {}^{2} - 5a + 8a - 40[/tex]
Answer:
[tex] = a {}^{2} + 3a - 40[/tex]
===========================================
[tex]2. (x - 4)(x - 8)[/tex]
[tex](x - 4) \times (x - 8)[/tex]
Multiply each term in the first parentheses by each term in the second parenthesis (FOIL).
[tex]x \times x - 8x - 4x - 4x( - 8)[/tex]
Calculate the product
[tex]x {}^{2} - 8x - 4x - 4x( - 8)[/tex]
[tex]x {}^{2} - 8x - 4x + 32[/tex]
Answer:
[tex] =x {}^{2} - 12x + 32[/tex]
===========================================
#CarryOnLearning